Lack of Interest in Reading Can Have a Negative Impact on Academic Achievement - Anita Candra Dewi; Rianti; Nurul Awalyah Rachman; Muh Al Imran; Rezki; Nasrul Haq Almadani (International Journal of Global Sustainable Research, 2023)
Interest in reading is an urge to understand word for word and the content contained in the reading text, so that readers can understand the things stated in the reading. Lack of interest in reading among students, especially university students. Even though reading will influence thinking patterns, the scope of learning activities in college is wider and deeper than studying at previous schools. Of course this will affect academic achievement. By collecting data by studying several related theories. And the result is that students' low interest in reading will cause a decrease in their ability to think, work, be passive, and play a less active role in learning so that their academic achievements are also less.